India my love - Lapierre, Dominique (New Delhi : Full Circle, 2013)
This is the extraordinary story of Dominique lapierre$1 (Bs love affair with India, from his first 20, 000 kilometre drive across the subcontinent in a veteran silver cloud Rolls-Royce gathering unique testimonies for his epic account of India$1 (Bs independence, to his later encounters with the country disinherited and its saints, who taught him a wonderful lesson in sharing and hope and gave birth to the internationally renowned book and film, (3z(Bthe city of joy(3y(B. it is a tale of maharajas and rickshaw pullers, of interviews with Indira Gandhi and the brother of Gandhian assassin, of life-changing meetings with mother Teresa and the victims of the Bhopal disaster, of pig sticking on horseback, of life in the slums with a Swiss nurse, and of saving a home for children affected by Leprosy. Above all, it is an insight into how India, with its immense mosaic of people and fascinating culture stole a frenchman$1 (Bs heart and turned his life into a testimony to the fact that (3z(Ball that is not given is lost(3y(B.s
Keywords: History -- 20th century. -- India; Social life and customs -- 20th century. -- India; Description and travel. -- India